Study on Design Method of Pile Wall Combination Structure in a Deep Foundation Pit Considering Deformation Induced by Excavation - Changjiang Wu; Changjiang Wu; Jun Yu; Xiaojian Cao; Wuqin Shen (Frontiers in Earth Science, 2022)
The technology of pile wall combination in a deep foundation pit is a kind of technology to resist soil and water pressure by using the great stiffness of the retaining pile and basement wall. As a part of basement wall, the retaining pile can reduce the thickness of the basement wall. However, the influence of excavation deformation and the interaction mechanism between the retaining pile and basement wall are ignored in the current design theory of the pile wall combination in a deep foundation pit. Therefore, we proposed a composite structure model of an elastic subgrade beam associated with a continuous beam, and introduced an elastic spring to simulate the interaction between the pile and basement wall. The finite difference equation and calculation method were established to figure out the internal force and displacement of the pile wall combination structure, which was able to accurately calculate the internal force and deformation of the retaining pile during the excavation stage. Based on the above results, further investigation was carried on the interaction between the pile and basement wall during the construction and normal service stage of the basement structure. It was concluded that the basement wall could reduce the lateral displacement on the top of the retaining pile caused by removal of the strut and affect the bending moment of the upper part of the retaining pile among the depth of the basement wall. The bending moment of the basement wall was closely related to the deformation of the retaining pile and changes with the working condition. In addition, the results of factor sensitivity analysis showed that the pile-wall relative stiffness ratio, stiffness of the horizontal beam, and slab of the basement had a significant influence on the interaction between the pile and basement wall.